The Rhetorical Construction of Female Empowerment: The Avenging-Woman Narrative in Popular Television and Film - (:unkn) unknown (My University, 2013)
In this critical rhetorical analysis, I examine the contemporary avenging-woman narrative in popular television and film. As a rhetorical text, the avenging-woman narrative can be read as a representation of cultural constructions of female empowerment. In this project, I situate the contemporary avenging-woman narrative within the context of a contemporary third wave feminist culture, in order to articulate how the representations of female empowerment in the texts may be a negotiation of cultural tensions about feminism. The four primary texts chosen for inclusion within this study are made up of two television shows, Revenge (2011-present) and Veronica Mars (2003-2007), and two films, The Girl with the Dragon Tattoo (2011) and Colombiana (2011). Each text features a woman depicted as transgressing social norms of traditional female behavior, usually through violence and with the purpose of exacting some form of revenge. Throughout this dissertation, I argue that although the image of the avenging-woman can be read as representative of female empowerment, the narratives simultaneously portray her as a cautionary tale against subversion within the system. I critique the depiction of female empowerment at the intersection of violence, a lack of homo-social relationships, a representation of sexualized feminine strength, and the objectification of the female body via fetishized technology. An analysis of each theme shows the complications that arise with the linking of women and power in the avenging-woman narrative. The representation of female empowerment is thus ultimately hegemonic, serving to reinforce the system the protagonist is depicted in the narrative as attempting to subvert. Although offering a pleasurable tale of justice and revenge, the avenging-woman text is also an example of how a rhetoric of female empowerment is problematic when it does not support political changes within a patriarchal system.
Keywords: Avenging-Woman; Female Empowerment; Feminism; Hegemony; Media; Rhetoric